display | more...

There is a matrix A, calculate An.

There are two ways to go about this problem, matrix multiplication or the method I will outline here. You will have to make a decision about which way is faster, this should be faster for small symmetric matricies.

This method will work for real symmetric matrices, complex and non-symmetric matrices may not work.
From Brontosaurus: "It will work for Hermitian matrices, i.e. the conjugate of the transpose is equal to the matrix".

Say we have a matrix A.

Calculate the eigenvalues and hence the eigenvectors of the matrix A.

Normalize (or normalise) the eigenvectors.
Basically, make it so all the vectors' lengths are 1 by multiplying by a scalar. Where for a vector x length = x.x

With the eigenvectors e1, e2 . . . en, and eigenvalues λ1, λ2 . . . λn.

From the eigenvectors create a matrix E such that:

```    ( .  .  .  . )
E = ( e1 e2 .. en )
( .  .  .  . )
```
Calculate another matrix, E -1. If the matrix is real and symmetric E -1 = ET, otherwise you will have to work out E -1.

Create another matrix D such that:
```    ( λ1 .. ..  )
D = ( .. λ2 ..  )
( .. .. λn  )
```
Now, A = EDE -1 (I won't go into the proof).
Now, say calculate A2.

A2 = E D2 E -1.

Since D is such a simple matrix all the hard work is multiplying D2 by E an then E -1.

N.B. You cannot say EE -1 = Identity, since matrix multiplication is not commutative, i.e. AB ≠ BA (well, not always).

This may be better explained by an example, so here goes...

We have a nice symmetric matrix A (makes the maths easier).
```    ( 1 2 )
A = ( 2 1 )

```
If has eigenvectors, then there exists an x and eigenvalue λ such that Ax = λx.
Re-arranging:

Ax - λ x = 0
( A - λ I )x = 0 (where I is the identity matrix)

If the above is true then the determinant of ( A - λ I ) = 0.
```| (1-λ)  2   |
|   2  (1-λ) | = 0

(1-λ)2 - (2 * 2) = 0
(1-λ) = ± 2

Giving eigenvalues,

λ1 = -1
λ2 =  3

Now, to get the eigenvectors,

Substituting λ1 into ( A - λ I )

( 2  2 ) (e11)   ( 0 )
( 2  2 ) (e12) = ( 0 )

Giving, e1 = ( 1  )
( -1 )

Substituting λ2 into ( A - λ I )

( -2  2 ) (e21)   ( 0 )
(  2 -2 ) (e22) = ( 0 )

Giving, (e2) = ( 1 )
( 1 )

Phew, now, I'll only do the short check on these eigenvectors.

e1.e2 = Cos Θ / |e1| |e2|

e1 . e2 = (1*1) + (1*-1) = 0 = Cos Θ
Θ = 90o as expected.

Now, to normalize (or normalise)

For e1, length = √2
so now, e1 = ( 1  ) / √2
( -1 )

For e2, length = √2
so now, e2 = ( 1 ) / √2
( 1 )

Now, to construct our matrices, E E -1 and D

(  1/√2  1/√2 )
E = ( -1/√2  1/√2 )

(  1/√2 -1/√2 )
E -1 = ET  = (  1/√2  1/√2 )

( -1  0 )
D = (  0  3 )

Phew, all done, now just a check.

A = E D E -1

(  1/√2  1/√2 ) ( -1  0  )
A = ( -1/√2  1/√2 ) (  0  3  ) E -1

( -1/√2  3/√2 ) (  1/√2 -1/√2 )
A = (  1/√2  3/√2 ) (  1/√2  1/√2 )

( (-1/2 + 3/2) ( 1/2 + 3/2) )   ( 1 2 )
A = ( ( 1/2 + 3/2) (-1/2 + 3/2) ) = ( 2 1 ) As expected.

Hurrah ! Now, use this method for big values of n !
```
Hope that you find this method useful, and sorry about the notation, HTML doesn't make it easy for me.
I did this (correctly) on paper before hand, please inform me of any errors I made typing this up.

Thanks to Brontosaurus who pointed this out: "2 vectors are orthonormal if their scalar product is 0 and they both have norm 1", this:"if there is not an orthonormal basis of eigen vectors then you will have to invert E", and this: "Your method is sure to work for any real symmetric (or complex hermitian) matrix, in other cases you may have to invert E".